ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH DAN LOYALITAS NASABAH BANK BNI CABANG LONDON - Hari Adji, Roekma; Edy Supriyadi, Edy; Derriawan (SEKOLAH PASCASARJANA PRESS, 2019)
The purpose of this study is to analyze the factors that built customer satisfaction to increase Bank BNI's customer loyalty at London branch. The factors studied were service quality, product quality, and customer trust. The statistical method for analyzing data is the structural equation model (SEM) from the Smart-PLS 2.M3 statistical package. The results of the study indicated that service quality, product quality, and customer trust had an effect on customer satisfaction directly. But service quality, product quality, and customer trust had no effect on customer loyalty directly, whereas indirectly through customer satisfaction, service quality, product quality and customer trust had an effect on customer loyalty. Customer loyalty is formed by a trust created in a mind of customers. Customer loyalty on a product should not trigger the customers to move its funds to other banks to invest, so it will benefit for both parties. Customer loyalty is a key factor in banking success. Customer Trust is a dominant factor that influence customer loyalty, increasing customer trust should make customers more loyal to BNI London branch such as by keeping its promise what has been said, prioritizing customer interest, and updating knowledge of its products. By understanding various aspects related to the form of trust as expected by customers and by increasing customer confidence are expected to increase customer loyalty in the future.